2021
DOI: 10.1016/j.sleep.2020.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Would we recover better sleep at the end of Covid-19? A relative improvement observed at the population level with the end of the lockdown in France

Abstract: Background The outbreak of the Covid-19 pandemic and the lockdown measures have had a major impact on societies around the world. This led to sleep problems for a large part of the population. In order to assess the sustainability of sleeping troubles related to the sanitary crisis, it was crucial to measure its prevalence after the end of the Covid-19 confinement. Method As a part of an epidemiological survey on Covid and Confinement (Coconel), we enquired on sleep dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…[134][135][136][137][138][139] Several weeks may be required before returning to a feeling of well-being consistent with that experienced prior to COVID-19. 2,132,[140][141][142] Selfisolation should continue to be practiced until resumption of regular daily activities is approved by a physician.…”
Section: Resultsmentioning
confidence: 99%
“…[134][135][136][137][138][139] Several weeks may be required before returning to a feeling of well-being consistent with that experienced prior to COVID-19. 2,132,[140][141][142] Selfisolation should continue to be practiced until resumption of regular daily activities is approved by a physician.…”
Section: Resultsmentioning
confidence: 99%
“…There is solid evidence, however, that insomnia often follows a persistent course [ 27 ] and, when it reaches a chronic status, it produces adverse health outcomes, such as enhanced risk of depression [ 28 ], prolonged leave of absences from work [ 29 ], and increased risk for hypertension [ 30 ]. It is also possible that milder form of sleep disturbances remit with the end of confinement as was observed with the end of the confinement following the first wave in France [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies across the world have also observed the remarkable effects of confinement on these three behaviors ( Colley et al., 2020 ; Dal Santo et al., 2021 ; Qin et al., 2020 ; Rolland et al, 2020 ; Smith et al., 2020 ; Wiederhold et al., 2020 ). Moreover, a longitudinal study found a trend towards the disappearance of the sleep disturbances after the lockdown release in France ( Beck et al., 2021 ). Being able to leave the house, either to work, entertain or play sports, seems to be a key change to organize personal routines, which in turn would help to restore sleep-wake rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rapidly changing nature of the COVID-19 pandemic, repeated measurements would provide a better insight on the dynamics of its consequences and their relationship with risk and protective factors. For instance, improvement in sleep problems ( Beck et al., 2021 ), increased physical activity ( McCarthy et al., 2021 ), and worsened feelings of loneliness ( Killgore et al., 2020 ) have been described several months after the confinement across the world.…”
Section: Introductionmentioning
confidence: 99%